2020
DOI: 10.1186/s12877-020-01853-9
|View full text |Cite
|
Sign up to set email alerts
|

“A false sense of confidence” The perceived role of inflammatory point-of-care testing in managing urinary tract infections in Dutch nursing homes: a qualitative study

Abstract: Background Diagnosing urinary tract infections (UTI) in nursing home residents is complex, due to frequent non-specific symptomatology and asymptomatic bacteriuria. The objective of this study was to explore health care professionals’ perceptions of the proposed use of inflammatory marker Point-Of-Care Testing (POCT) in this respect. Methods We conducted a qualitative inquiry (2018–2019) alongside the multicenter PROGRESS study (NL6293), which assessed the sensitivity of C-reactive protein and procalcitonin … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Physicians and nurses were reported in that study. A survey was conducted to test the importance of “point-of-care testing” (POCT) as a UTI diagnosing technique at nursing resident homes [ 12 ]. Information on the ten included studies in this systematic review is presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Physicians and nurses were reported in that study. A survey was conducted to test the importance of “point-of-care testing” (POCT) as a UTI diagnosing technique at nursing resident homes [ 12 ]. Information on the ten included studies in this systematic review is presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Study designs of included articles are shown in the second column of Table 2 . Studies [ 12 , 14 , 16 , 17 , 20 , 21 ] were mainly focused on diagnosing UTIs in patients, while studies [ 18 , 19 ] investigated the treatment approaches of UTI patients. The rest of the studies [ 13 , 15 ] assessed UTI prophylaxis and asymptomatic bacteriuria (UTI), as shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As our trial was not designed for assessment of these purposes, possibly, future studies could focus on CRP-values related to prognosis and monitoring along the disease trajectory. 11,36,37 Some studies described CRP POCT as a "learning tool to detect patients needing antibiotics," through improved clinical pattern recognition. 37,38 Similar to other studies, physicians in this study believed that CRP POCT reinforced their diagnostic toolkit, while they were also cautious toward over-reliance.…”
Section: Barriers and Facilitatorsmentioning
confidence: 99%
“…37,38 Similar to other studies, physicians in this study believed that CRP POCT reinforced their diagnostic toolkit, while they were also cautious toward over-reliance. 36,38…”
Section: Barriers and Facilitatorsmentioning
confidence: 99%